(untitled) (Scientific journal of the Fergana State University, 2026)
The growth and development of plants occur as a result of the formation of a complex network of genes present in their genome. Such intricate interactions contribute to the morphological advancement of plants. There are several pathways for gene interaction, and one of these mechanisms is represented by Cis-Acting Elements (CAE) or cis-regulatory modules (CRM). Studying CRM functions is an important tool for investigating gene expression. Despite the achievements in high-quality genome sequencing and annotation of plant genomes using modern technologies, the identification of CRM, the understanding of their functions, and their role in gene expression regulation remain insufficiently explored. In this study, in silico bioinformatic analyses were conducted to identify CRM in transcripts of members of the GhFHY3/FAR1 gene family in upland cotton (Gossypium hirsutum L.). The in silico analysis of the transcripts revealed that members of this family are involved in the regulation of gene expression controlling light signaling and hormonal systems, including gibberellins, auxins, and cytokinins. These hormonal systems regulate not only plant growth and development but also mechanisms of resistance to abiotic and biotic factors. The results of this research indicate that the identified CRM in transcripts of GhFHY3/FAR1 gene family members of cotton (G. hirsutum L.) play a role in regulating plant resistance mechanisms against adverse environmental conditions.